PELAYANAN PEMBUATAN AKTA KELAHIRAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SANGGAU - Lorensius Mus E.21110100 (FISIP Universitas Tanjungpura, 2013)
This article was about Birth Certificate service at Demography and Civil inscription Office of Sanggau Regency. This research was conducted to expose the problem of birth certificate service nowadays by the rules, regulation and procedures, infrastructure and employee at Demography and Civil inscription Office of Sanggau Regency. The problem was interested to expose because there were a lot of people in Sanggau Regency still have not the birth certificate whereas each people must keep the birth certificate itself. Undang-undang nomor 23 Tahun 2006 about Civil Administration, Undang-undang nomor 23 Tahun 2002 about Children Protection said that every child has the right to their identity and nationality. Nowadays there were so many people did not know to get the birth certificate so people participated to get the birth certificate was low. Trough this article the researcher hoped the problems of birth certificate servise nowadays by rules, regulation and procedures, infrastructure and employee at Demography and Civil inscription Office of Sanggau Regency whould be increased. Keywords: Birth certificate, regulation and procedure, infrastructure and employee.